Development of a selectable teleoperated robot system using RSNP - Ishida, Shinichi; Ogiya, Hiroshi; Matsuhira, Nobuto (2014 11th International Conference on Ubiquitous Robots and Ambient Intelligence (URAI), 2014)
A teleoperated robot system communicating through a robot service network protocol (RSNP) has been developed. In this system, robots and operation devices are freely selected among registered robots and operation devices, respectively. Robots can be interchanged to suit the target task. Thus, we aim to build a suitable teleoperated robot system for specified tasks. Here, we introduce the developed system and the results of basic robot surfing experiments. We also discuss a common GUI for multiple robot systems.